Re-allocating taxing rights and minimum tax rates in international profit taxation - Gerhard Kempkes; Nikolai Stähler (Deutsche Bundesbank, 2021)
What are the macroeconomic implications of re-allocating taxing rights away from source countries (where goods are produced) to market countries (where goods are consumed) and introducing minimum rates in international profit taxation? We assess this question in a dynamic macroeconomic model that gives a meaningful role to profit taxation. We find that, in low tax economies, the average profit tax rate will rise. On the one hand, this reduces price competitiveness of firms located in these regions and, thereby, output. On the other hand, higher profit tax revenues help to reduce other taxes. Moreover, lower expected future output requires less capital in production in the long run. Firms hence invest less and (temporarily) augment dividend payments. This raises disposable income of households, who (at least temporarily) increase consumption. The opposite holds for high tax economies. When taxing rights are re-allocated, wealth transfers between regions mitigate these effects. In terms of welfare, low tax economies can benefit from an increase in profit taxation.
Keywords: H25; L52; E20; E62; L10; 330; Re-Allocating Profit Taxing Rights; Minimum Taxation; InternationalMacro